2011
DOI: 10.1007/s12253-011-9395-6
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1 Promoter Methylation in Primary Colorectal Carcinoma

Abstract: TWIST1 gene, a transcription factor that belongs to the family of basic helix-loop-helix proteins, has been related to tumor progression and metastasis in different cancers. The aim of our study was to investigate TWIST1 promoter methylation in patients with primary colorectal carcinoma and determine its correlation with prognostic factors and disease outcome. Seventy-three patients with primary colorectal adenocarcinoma were studied. From each patient two tissue samples were collected: one sample of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…Moreover, Ashktorab and colleagues, performing an extensive bioinformatics work on CpG island Methylator Phenotype, identified TWIST1 as markedly hypermethylated in colorectal cancer [31]. Other groups report methylation percentages of >40% across these tumors [32, 33]. Our results confirm these findings not only for TWIST1 but also TWIST2.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, Ashktorab and colleagues, performing an extensive bioinformatics work on CpG island Methylator Phenotype, identified TWIST1 as markedly hypermethylated in colorectal cancer [31]. Other groups report methylation percentages of >40% across these tumors [32, 33]. Our results confirm these findings not only for TWIST1 but also TWIST2.…”
Section: Discussionsupporting
confidence: 86%
“…We observed lack of correlation between hypermethylation and protein expression in normal colorectal mucosa may suggest that hypermethylation as a regulatory mechanism of TWIST1 and TWIST2 may be restricted to the tumor microenvironment. These results are supported by others [25, 33]. Other mechanisms of TWIST1 regulation in normal tissue may include post-translational histone modifications, however this aspect still remains to be elucidated.…”
Section: Discussionsupporting
confidence: 84%
“…Of these, 118 targets samples. [20][21][22] Deleted in colon cancer (DCC) methylation is a frequent event in CRC, and three independent studies have found high rates (82%, 80%, and 56%) of DCC promoter methylation in primary and sporadic CRC using MSP, COBRA, and qMSP approaches, respectively. [23][24][25][26][27][28] Genome-wide analysis have cited Receptor Protein Tyrosine Phosphatase Delta gene (PTPRD) as hypermethylated in CRC and a predictor of poor prognosis, 12 an observation that was previously corroborated by our laboratory in Iranian and African American populations.…”
Section: Resultsmentioning
confidence: 99%
“…TWIST, which is frequently overexpressed or hypermethylated, has important implications for tumor metastasis in colon cancer [31, 32]. It is therefore important to understand the role of upstream TWIST regulation in production and regulation pathways, and how it might provide benefits in terms of early cancer treatment [33].…”
Section: Discussionmentioning
confidence: 99%